Entre cartilhas metodológicas e inventividade dos técnicos do CRAS : a prática de fortalecimento de vínculos - Barreto, Danilde Figueiredo (2015)
This Work aims to analyse the concepcions and practices of bond strenghtening done by CRAS employees. From this, thinking about the forces involved in their actions and it´s consequences was crucial. From this, we attempted to reflexo on the different factors that may influence their actions and its possibles outcomes. To do so, a research that was inspired by the etnographic aproach was made, wich started in an imersion i had in a different CRAS from 2011 to 2012. To evaluate this theme, field diaries were used, wich contained some interviews with CRAS psychologists, social workers and social educators. In addition to that, the official methodological manuals (instruments of normalization and orientation to all professionals that base their work on the SUAS) were read and analysed. The bond strengthening in social communities and families are described as an action in which technicians are supposed to help patients to prevent social risks and vulnerabilities in a specific area. Solely basing on the diferent concepts of bond, community and family, we saw how these definitions are responsible for diferent social practices. These practices were in most cases totalizing, permanent and universal, what forced us to question and dismember them in order to reflect about what is being produced from the SUAS theories. It was also pointed that there are many challenges when trying to strenghenten bonds and the inventive ways of this work.